1968
DOI: 10.1017/s0021859600012740
|View full text |Cite
|
Sign up to set email alerts
|

The growth of vining peas: I. The effect of time of sowing

Abstract: Yield and growth analysis have been applied to the results of an experiment comparing early and late sown peas. Yield analysis showed that in this experiment late sown peas had:(i) fewer podding nodes per main stem, (ii) fewer pods per podding node, and (iii) a slower rate of increase in pod weight. The physiological origins of these differences are discussed.The first component is determined by the stage at which node production is terminated by the death of the apical bud.The second is determined by morphoge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

1978
1978
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 15 publications
1
9
0
Order By: Relevance
“…The present study also indicated that delaying sowing in spring until mid-April resulted in large yield reductions compared with March sowings, which is in agreement with the findings of many workers (Boswell, 1926;Kruger, 1973;Milbourn & Hardwick, 1968;Proctor, 1963;Salter & Williams, 1967). These workers attributed the reduction in yield from delayed sowings to one or more of the following: water stress, high temperature, or a shortened growing season.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The present study also indicated that delaying sowing in spring until mid-April resulted in large yield reductions compared with March sowings, which is in agreement with the findings of many workers (Boswell, 1926;Kruger, 1973;Milbourn & Hardwick, 1968;Proctor, 1963;Salter & Williams, 1967). These workers attributed the reduction in yield from delayed sowings to one or more of the following: water stress, high temperature, or a shortened growing season.…”
Section: Discussionsupporting
confidence: 92%
“…Con-N. America are spring sown. Most sowing-date field sequently, there is a growing interest in autumn trials have, therefore, concentrated on spring sow-sowing of combining peas in the U.K. ings and excluded autumn sowings (Boswell, 1926; Winter-hardy pea varieties are autumn sown in Fletcher et al 1966;Milbourn & Hardwick, 1968; S. Europe. Autumn-sown crops already established Proctor, 1963;Vulstekeg, 1974).…”
mentioning
confidence: 99%
“…Yield reductions from the later sowing date occurred even under the HM treatment, where water cannot have been limiting, as has also been shown for leafed green peas by Salter & Williams (1967). It has been suggested that high temperatures may be a cause of yield reductions in (Milbourn & Hardwick 1968) and temperatures greater than 25 or 26 C C at the time of flowering or pod filling have been shown to reduce seed yields (Lambert & Linck 1958;Pumphrey et al 1979). However, this does not appear to have been a cause in this investigation, when such high temperatures were rare.…”
Section: Discussionmentioning
confidence: 76%
“…1984). Moisture stress has also been suggested as a factor which may contribute to yield reductions in late-sown crops, greater soil moisture deficits being developed by the time the critical growth stages are achieved (Milbourn & Hardwick 1968). However, Salter & Williams (1967) indicated that this is not the only factor, as yield reductions with successive sowing dates were found even in peas irrigated at flowering and at pod filling.…”
Section: Introductionmentioning
confidence: 99%
“…The low yields were associated with low numbers of podding nodes/stem and pods/node and a slower increase in pod weight (Milbourn & Hardwick 1968). Whether these changes would affect the balance between sources and sinks is uncertain.…”
Section: Discussionmentioning
confidence: 99%